A Note on Solvability of the Nonlinear Abstract Viscoelastic Problem in Banach Spaces (Journal of Partial Differential Equations, 2020)
In this work we are concerned with the existence of integral solution for a nonlinear abstract viscoelastic problem in Banach space, where the operator is accretive dependent on time.